Altai alphabet with cyrillic graphics - DİLBƏR (Uluslararası Türk Lehçe Araştırmaları Dergisi)
During the Tsarist Russia and later during the Soviet era, the Altai Turks also had difficulty with the alphabet process, like other Turkic peoples. Tsarist Russia used these alphabets, called the "missionary alphabet" in Turkology, to bring the Turkic peoples under its rule and assimilate them as it wished. The Altai alphabet with Cyrillic graphics was one of them. Of course, this alphabet had negative and positive sides. Although the adoption of these alphabets accelerated the literacy process among the Altai Turks, the repeated changes of the alphabet by the commission caused contradictions. The article analyzes the adoption process of the Cyrillic Altai alphabet and the negative and positive sides of this alphabet. The spelling of the Altaic language has been in use since the 19th century. In Siberia, unlike many living peoples, writing in the Altai language began in the 40s of the 19th century appeared and acertain part of the literature written in this script was formed.The writing of the Altai language was compiled by representatives of the Altai spiritual mission. When designing the Altai alphabet, representatives of the Altai spiritual mission they had one main goal in mind. This was to convert the Altaic Turks.